MRSI‐based molecular imaging of therapy response to temozolomide in preclinical glioblastoma using source analysis. (8th April 2016) - Delgado‐Goñi, T.; Ortega‐Martorell, S.; Ciezka, M.; Olier, I.; Candiota, A. P.; Julià‐Sapé, M.; Fernández, F.; Pumarola, M.; Lisboa, P. J.; Arús, C.
Abstract : Characterization of glioblastoma (GB) response to treatment is a key factor for improving patients' survival and prognosis. MRI and magnetic resonance spectroscopic imaging (MRSI) provide morphologic and metabolic profiles of GB but usually fail to produce unequivocal biomarkers of response. The purpose of this work is to provide proof of concept of the ability of a semi‐supervised signal source extraction methodology to produce images with robust recognition of response to temozolomide (TMZ) in a preclinical GB model. A total of 38 female C57BL/6 mice were used in this study. The semi‐supervised methodology extracted the required sources from a training set consisting of MRSI grids from eight GL261 GBs treated with TMZ, and six control untreated GBs. Three different sources (normal brain parenchyma, actively proliferating GB and GB responding to treatment) were extracted and used for calculating nosologic maps representing the spatial response to treatment. These results were validated with an independent test set (7 control and 17 treated cases) and correlated with histopathology. Major differences between the responder and non‐responder sources were mainly related to the resonances of mobile lipids (MLs) and polyunsaturated fatty acids in MLs (0.9, 1.3 and 2.8 ppm). Responding tumors showed significantly lower mitotic (3.3 ± 2.9 versus 14.1 ± 4.2 mitoses/field) and proliferation rates (29.8 ± 10.3 versus 57.8 ± 5.4%) than control untreated cases. The methodology described in this work is able to produce nosological images of response to TMZ in GL261 preclinical GBs and suitably correlates with the histopathological analysis of tumors. A similar strategy could be devised for monitoring response to treatment in patients. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The methodology described in this work is able to characterize the response to TMZ in preclinical GB both at a defined time point and in real time, throughout the therapy protocol. The response patterns detected correlate well with the histopathological analysis of control and treated tumors at each stage. This strategy has translational potential for monitoring patient response to treatment.